Pengembangan Media Pembelajaran Terintegrasi Budaya Motif Batik Berbasis Augmented Reality (AR) - Rani Nurhidayah; Suyitno Suyitno; Nila Kurniasih (Ideguru: Jurnal Karya Ilmiah Guru, 2025)
Inclusive education continues to face challenges in providing appropriate learning media for students with learning difficulties. Traditional, non-interactive teaching methods often hinder student engagement and understanding of the concepts being taught. This study aims to develop mathematics learning media based on Augmented Reality (AR) integrated with traditional batik motifs from Central Java. This innovation is designed not only to enhance students’ conceptual understanding through more visual and engaging learning experiences but also to foster appreciation for local cultural heritage. The research employed a Research and Development (R&D) approach consisting of ten stages, from information gathering to product dissemination. The subjects were students with learning difficulties at SMP Negeri 19 Purworejo. Data were collected through observation, questionnaires, and interviews, then analyzed using qualitative and quantitative approaches. The results show that the AR-based learning media featuring batik motifs were successfully developed with a simple design, interactive display, and content suited to students’ needs. The feasibility test produced an average score of 4.26 (very good category), indicating that the media are suitable in terms of accessibility, visual design, and content completeness. Furthermore, the use of this media effectively improved students’ understanding and learning motivation through enjoyable interactive experiences while contributing to the preservation of local culture.